Research on Dependable Ionizing Radiation Protection based on Model i* - Tan Hai; Shahnawaz Talpur; Imran Ali Qureshi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The software’s unreliability mostly attributes to an erroneous analysis on the requirements done at the beginning. In this paper, we apply the tool of i* frame requirement modeling and build early requirement model against ionizing radiation. After finding out possible risks and corresponding solutions during the process of modeling analysis, we propose reasoning models against ionizing radiation. The radiation protection system  with  the  above models  can  figure out  the  purpose  of agents  related  to radiant source and provide normal service even when the environment software system is being interfered. It can serve the ecological and economical society with stability and development.  The model is divided into several sections. Section 1 gives the outline of the dependant software. Section 2 illustrates the  i* frame  technology. Section 3, 4 and 5 cover the topic of dependant security requirement analysis, SD&SR model on ionizing radiation respectively. Section 6 gives the conclusion. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2020